Improving antioxidant function, inflammatory responses, growth performance, and mortality by supplementing black cumin (Nigella Sativa) seed in broiler chickens exposed to low ambient temperature - Fathi, M; Zarrinkavyani, K; Biranvand, Z; Mohmmadi, Y; Jameel Hilal, M (Journal of the Hellenic Veterinary Medical Society, 2025)
This study was done to investigate the effects of black cumin (Nigella sativa) powder (BCP) on oxidative stress, inflammation cytokines, hematological and biochemical change and growth performance of broilers under low ambient temperature. Total of 375 one -day-old male Ross 308 broilers were randomly allocated into five treatments with five replication pens (with 15 broilers per pen). A total of 75 birds were reared in a thermoneutral (TN group) environment, and the rest of the birds (300 birds in four groups) were exposed to cold stress (CS). On d 14, CS birds' groups were fed a control diet and three levels of BCP at rates of 5, 10, and 15 g/kg (BCP-5, BCP-10, and BCP-15, respectively). The blood and heart samples were collected. On day 42, two birds per cage (n = 10/treatment) were weighed and euthanized, and samples for blood and heart were collected. Dietary BCP modulated cold-induced effects on growth performance indices, relative weight heart weight, right ventricle / total ventricle ratio, right ventricle /body weight and mortality. The activities of superoxide dismutase, catalase, and glutathione peroxidase in serum and liver were enhanced, and malondialdehyde was reduced by BCP supplementation compared to the CS group. The cold stress-induced effect on serum and liver levels of TNF-α and interleukin-6 were reduced, and interleukin-10 was enhanced by dietary BCP supplementation. Moreover, supplementing of diets with BCP alleviated the adverse effect of cold stress as reflected by a reduction in alanine transaminase, aspartate transaminase, alkaline phosphatase, triglyceride, and cholesterol compared to the CS group. In conclusion, BCP supplementation during cold stress may be used to alleviate cold stress- related changes in broiler chickens.